2018
DOI: 10.7717/peerj.5967
|View full text |Cite
|
Sign up to set email alerts
|

Stress among on-duty firefighters: an ambulatory assessment study

Abstract: BackgroundStress at work has been broadly acknowledged as a worldwide problem and has been the focus of concern for many researchers. Firefighting, in particular, is frequently reported as a highly stressful occupation. In order to investigate firefighters’ occupational health in terms of stress events, perceptions, symptoms, and physiological reactions under real-world conditions, an ambulatory assessment protocol was developed.MethodsSeventeen firefighters’ cardiac signal was continuously monitored during an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 34 publications
2
31
0
1
Order By: Relevance
“…One found significant relationships between greater basal RMSSD and two computerized cognitive stress tests, as well as during recovery from those tasks (38). The last study found a significant decrease in AVNN at the start of a two-choice critical reaction time task and a significant change in LF/HF ratio following the task (43).…”
Section: Cognition Testingmentioning
confidence: 85%
See 4 more Smart Citations
“…One found significant relationships between greater basal RMSSD and two computerized cognitive stress tests, as well as during recovery from those tasks (38). The last study found a significant decrease in AVNN at the start of a two-choice critical reaction time task and a significant change in LF/HF ratio following the task (43).…”
Section: Cognition Testingmentioning
confidence: 85%
“…Selected publications included males only in 11 studies, both males and females in seven studies and the gender distribution was not reported in three studies. Seven tactical subpopulations were represented; general law enforcement officers ( 32 , 33 ), Army ( 27 , 29 , 31 , 34 36 , 46 ), Defense Force trainees ( 37 ), Naval cadets ( 38 ), Army Ranger trainees ( 39 ) firefighters/rescue personnel ( 28 , 30 , 40 , 41 , 43 , 45 ), and Air Force fighter pilots ( 42 ). Specifically, the Army personnel were members of either the US, Brazilian or Spanish militaries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations